Therapeutic Effects of Melatonin on Ocular Diseases: Knowledge Map and Perspective - Yu, Haozhe; Wang, Qicong; Wu, Wenyu; Zeng, Weizhen; Feng, Yun (Frontiers in Pharmacology, 2021)
Melatonin plays a critical role in pathophysiological process including circadian rhythm, apoptosis and oxidative stress. It can be synthesized in ocular tissues, and its receptors are also found in the eye, triggering more investigations concentrated on the role of melatonin in eye. In the past decades, the protective and therapeutical potentials of melatonin for ocular diseases have been widely revealed in animal models. Herein, we construct the knowledge map of melatonin in treating ocular diseases through bibliometric analysis and review its current understanding and clinical evidences. The overall field could be divided into twelve topics through keywords co-occurrence analysis, in which the glaucoma, myopia and retinal diseases were of greatest research interests according to the keywords burst detection. The existing clinical trials of melatonin in ocular diseases mainly focused on the glaucoma, and more research should be promoted especially for various diseases and drug administration. We also discuss the its bioavailability and further research topics including developing melatonin sensors for personalized medication, acting as stem cell therapy assistant drug and intaking food-derived melatonin for facilitating its clinical transformation.